Évolution théorique en criminologie : l’histoire d’un cheminement - Landreville, Pierre (Criminologie, 1986)
Based on the author's personal experience, he proposes consideration of the theoretical choices offered Montreal criminologists over the past 25 years. At first, the sole object of criminology was the etiology and social treatment of crime. At the end of the 60's and for the following ten years or so, there were many expressions of doubt both at the socio-political level as well as concerning the social sciences and criminology as such. The movements for the defence of minority rights and new theoretical orientations led the author to question the production of norms and attribution of the «quatity» of deviant rather than the factors of delinquency. He explains here how from a criminology of acting out he eventually arrived at a criminology of social control. More in-depth analyses of punishment and penal justice led the author to question the very existence of the entire criminal justice system and, like L. Hulsman, to take an abolitionist position. He then describes how he conceives the role of the clinician in this perspective.